Comparison Between Numerical Analysis and Actual Results for a Pull-Out Test - GONTARZ, Jakub; PODGÓRSKI, Jerzy; JONAK, Józef; KALITA, Marek; SIEGMUND, Michał (Engineering Transactions, 2019)
The paper describes a computer analysis of the pull-out test used to determine the force needed to pull out a fragment of rock and the shape of this broken fragment. The analyzed material is sandstone and porphyry. The analysis included a comparison of different methods of propagation of cracks in the Abaqus computer program using the Finite Element Method. The work also contains a description of laboratory tests and analytical considerations.